What is the prevalence of COVID-19 detection by PCR among deceased individuals in Lusaka, Zambia? A postmortem surveillance study. Issue 12 (6th December 2022) - Gill, Christopher J; Mwananyanda, Lawrence; MacLeod, William B; Kwenda, Geoffrey; Pieciak, Rachel C; Etter, Lauren; Bridges, Daniel; Chikoti, Chilufya; Chirwa, Sarah; Chimoga, Charles; Forman, Leah; Katowa, Ben; et al.
Abstract : Objectives: To determine the prevalence of COVID-19 postmortem setting in Lusaka, Zambia. Design: A systematic, postmortem prevalence study. Setting: A busy, inner-city morgue in Lusaka. Participants: We sampled a random subset of all decedents who transited the University Teaching Hospital morgue. We sampled the posterior nasopharynx of decedents using quantitative PCR. Prevalence was weighted to account for age-specific enrolment strategies. Interventions: Not applicable—this was an observational study. Primary outcomes: Prevalence of COVID-19 detections by PCR. Results were stratified by setting (facility vs community deaths), age, demographics and geography and time. Secondary outcomes: Shifts in viral variants; causal inferences based on cycle threshold values and other features; antemortem testing rates. Results: From 1118 decedents enrolled between January and June 2021, COVID-19 was detected among 32.0% (358/1116). Roughly four COVID-19+ community deaths occurred for every facility death. Antemortem testing occurred for 52.6% (302/574) of facility deaths but only 1.8% (10/544) of community deaths and overall, only ~10% of COVID-19+ deaths were identified in life. During peak transmission periods, COVID-19 was detected in ~90% of all deaths. We observed three waves of transmission that peaked in July 2020, January 2021 and ~June 2021: the AE.1 lineage and the Beta and Delta variants, respectively. PCR signals were strongest among those whose deaths were deemed 'probably due to COVID-19', and weakest among children, with an age-dependent increase in PCR signal intensity. Conclusions: COVID-19 was common among deceased individuals in Lusaka. Antemortem testing was rarely done, and almost never for community deaths. Suspicion that COVID-19 was the cause of deaths was highest for those with a respiratory syndrome and lowest for individuals <19 years.